PEMBENTUKAN DAN TRANSFORMASI CORE VALUES DI SEKOLAH ALAM - Fauzi, Fauzi (JIV-Jurnal Ilmiah Visi, 2018)
Research background by the phenomenon of the success of the School of Nature in realizing its existence as one of the alternative educational institutions in Indonesia. The success is based on its ability to form and transform its core values. This study aims to describe the process of formation and transformation of core values based on environmental peculiarities and local wisdom in the School of Nature Baturraden (SABar). The study was conducted in February - August 2017 at SABar located within the Damar forest of Baturraden campground. This research used a qualitative approach and collected data by observation, interview, and documentation technique. The data were analyzed by the interactive model of qualitative analysis technique, including data collection, data reduction, data presentation, and conclusion drawing. This research showed that all education and learning activities are conducted by the integrative holistic approach by making the forest to a place, source, and learning media in the process of awareness, enlightenment, empowerment, character and behavior building of the children. Core values developed by Baturraden Nature School are based on five SABar values that are soulful, morals, beyond, achieve, and responsible. These values become distinctive values and differentiator with other nature schools and become a brand of Baturraden nature school. In addition, the school embodies four dimensions of core values agreed upon in the national network of nature school, which are curriculum, method, environment, physical, and community. References Baharudin. (2014). Gagasan Ivan Illich tentang pendidikan dalam buku deschooling society. Terampil, 2(2), 118-151. https://anzdoc.com/gagasan-ivan-illich-tentang-pendidikan-dalam-buku-deschoolin.html Collins, J. (2014). Good to great. Jakarta: Gramedia Pustaka Utama. Dewey, J. (2009). Pendidikan dasar berbasis pengalaman. Yogyakarta: I Publishing. Freire, P. (1984). Pendidikan sebagai praktek pembebasan, terjemahan Alois A. Nugroho. Jakarta: Gramedia. Freire, P. (2000). Pendidikan kaum tertindas. Jakarta: LP3ES. Diakses dari http://sekolahalam.id/alam. Illich, In. (2005). Bebaskan masyarakat dari belenggu sekolah. Jakarta: Yayasan Obor Indonesia. Pella, D.A. (2008). Semuanya bermula dari core values. Diakses melalui https://darminpella.wordpress.com Reimer, E. (1987). Sekitar eksistensi sekolah: Sebuah essay tentang alternatif-alternatif pendidikan. Yogyakarta: Hanindita. Sadulloh, U. (2015). Pengantar filsafat pendidikan. Bandung: Alfabeta. Safar, M. (2015). Sekolah di atas awan. Bandung: Thabi’ Press. Strauss, A., dan Corbin, J. (2003). Dasar-dasar penelitian kualitatif. Yogyakarta: Pustaka Pelajar. Sugiono. (2014). Metode penelitian. Bandung: Alfabeta. Tilaar, H.A.R. (2009). Kekuasaan dan pendidikan: Manajemen pendidikan nasional dalam pusaran kekuasaan. Jakarta: Rineka Cipta. Tilaar, H.A.R. (2012). Perubahan sosial dan pendidikan: Pengantar pedagogik transformatif untuk Indonesia. Jakarta: Rineka Cipta. Wardani, IG.A.K., dkk. (2014). Perspektif pendidikan SD. Jakarta: UT Press. Yahya, A. (2003). Great spirit, grand strategy corporate philosophy, leadership architecture, and corporate culture for sustainable growth. Jakarta: Gramedia.